Stress and meat quality in two lines of the Yorkshire pig breed: Swedish and Dutch - Andersson, Andreas (2019)
Pigs are exposed to several different environmental stressors in the modern production from weaning, mixing, crowding etc. Preslaughter stressors may result in meat quality problems, such as the formation of pale, soft and exudative meat as well as the formation of dark, firm and dry meat, which makes the meat to be unattractive. In 2012, the Swedish Yorkshire (SY) was replaced with the Dutch Yorkshire of the Z-line (ZY) for financial decisions as well as the ZY having a more efficient breeding progress in the ZY line. The SY has been indirectly selected for social behaviours to a larger extent compared to the ZY since the sows of the SY has been selected in group housed systems while the sows of the ZY have been housed individually. The aim of this pilot study is therefore to investigate if there are differences in stress related behaviours and meat quality between the SY and the ZY and between pigs provided with social training (access pen) early in life with pigs not allowed social training (control pen). The stress levels and meat quality were measured on in total of 60 pigs. Aiming to assess stress, a Novel Arena test and a Startle test were performed in the pig facility short before slaughter and a Novel Arena test was also performed at the slaughter plant. The lactate level in the blood and the temperature and pH of the carcass was measured at the slaughter plant. During the suckling period, half of the litters were in the access pen and had the opportunity to walk between two pens while the remaining stayed within their pen, control pen. The result showed that there were no significant differences in stress levels or meat quality between the breeds but the SY had a significant higher meat percentage (P=0.021) compared to the ZY, which may indicate that the ZY have a higher fat storage. If both of the breeds were kept in control pens during the suckling period, the ZY had a significant higher growth rate (P=0.008) and lower age at slaughter (P=0.008) compared to the SY. The pigs in the control pen performed significant more hesitation (P=0.01) and activity (P=0.038) compared to the pigs in the access pen in the Novel Arena test in the slaughter plant, which may indicate that the pigs in the control pen may have been more stressed. There was no significant difference in the meat quality for the different treatments. In conclusion, there is no significant difference in the stress levels and meat quality between the breeds. It may be a difference in stress levels between the treatments, where the pigs in the access pen and thus with extra social training were less stressed, but no significant difference between treatments was found for meat quality.